Evaluation of cadmium bioaccumulation and translocation by Hopea odorata grown in a contaminated soil - Abdu, Arifin; Ahmadpour, Parisa; Abdul Hamid, Hazandy; Tengku Muda Mohamed, Mahmud; Junejo, Nasima; Ahmadpour, Fatemeh; Soleimani, Mohsen; Wasli, Mohd Effendi; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2012)
Cadmium (Cd) contamination has an adverse effect on soil productivity and crop production. Phytoremediation is a long term and environmental friendly technology to remediate Cadmium polluted areas. This study was conducted to evaluate the potential of Hopea adorata for remediation of soils contaminated with Cd. Plant seedlings were planted in a clayey soil spiked contaminated with Cd in the amount of 0, 25, 50, 75, 100 and 150 mg kg-1 named as; Cd0, Cd1, Cd2, Cd3, Cd4 and Cd5 for a period of five months. The highest growth performance was recorded in the control (Cd0). Cd concentrations among plant parts were in the following trend: roots>stems>leaves. In order to evaluate the potential of species selected as phytoremediator, three indicators were used namely, bioconcentration factor (BCF, the metal concentration ratio of plant roots to soil), translocation factor (TF, the metal concentration ratio of plant shoots to roots) and removal efficiency (RE, total concentrations of metal and dry biomass of plants to total loaded metal in growth media). The highest total Cd concentration (290.23 ± 13.38 mg kg-1) and Cd removal efficiency (0.81± 0.06%) were found in Cd5 and Cd1, respectively. Cd2 exhibited the maximum total dry biomass (60.88 ± 1.78 g). H. odorata showed high BCFs (>1) and low TFs (<1). It can be concluded that this species is suitable to be used in phytoremediation of Cd-contaminated. For further confirmation, an evaluation under field condition will be needed.